(untitled) (Research, Society and Development, 2021)
This study aimed to analyze, through the literature, the scientific evidence that involves the processes of production and understanding of the nursing record in the hospital environment. It is an integrative literature review, in which the following question was asked: “What is the scientific evidence about the process of production and understanding of the nursing record in the hospital environment?”. A PICo strategy was set up, in which, through descriptors and keywords, the databases of the National Library of Medicine were consulted; VHL (Virtual Health Library), and CINAHL (Cumulative Index to Nursing and Allied Health Literature). Thirteen studies were included in this review. Most studies dealt with the key components for the elaboration of the medical record, emphasizing its purpose, quality and use in the hospital environment; the main conformities and non-conformities; the implications under rules and regulations; and the difficulties encountered by professionals regarding the sector and the assistance phase. Regarding the flaws in the nursing records, studies cited that most professionals are unaware of the institution’s requirements, the current legislation and the code of ethics. It is concluded that nursing professionals must adopt permanent training measures for correct adherence to medical records, seek resolution on fragmented service, and learn from their own mistakes, so that there are no complications in the actions to be performed with regard to the patient hospitalized.